2003
DOI: 10.1177/10298649040070s108
|View full text |Cite
|
Sign up to set email alerts
|

Beginnings and Endings in the Musical Improvisations of Children Aged 7 to 10 Years

Abstract: Many factors influence the activation and maturation of the compositional process in children. Although there are numerous studies on children's processes, production and behaviour, little has been done concerning the influence of the didactic strategies used by the teacher: which may actually encourage or suppress such processes.Children are generally asked to create a composition that has a beginning, a middle and end, but we wondered whether it was really necessaryto request this structure or if children of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In the 2009 study, however, main effects were found for treatment but not for grade level. Tafuri et al (2003) found that a certain percentage of Italian children aged 7 years could already improvise a musical beginning and ending, even without instruction, and that this skill improved as age increased. They recommended that teachers first verify the extent to which their students could already improvise beginnings and endings and to use that as a starting point for teaching this skill.…”
Section: Development Of Improvisation Skills With Agementioning
confidence: 96%
See 1 more Smart Citation
“…In the 2009 study, however, main effects were found for treatment but not for grade level. Tafuri et al (2003) found that a certain percentage of Italian children aged 7 years could already improvise a musical beginning and ending, even without instruction, and that this skill improved as age increased. They recommended that teachers first verify the extent to which their students could already improvise beginnings and endings and to use that as a starting point for teaching this skill.…”
Section: Development Of Improvisation Skills With Agementioning
confidence: 96%
“…Several researchers have examined the specific developmental abilities of elementary children's improvisation skills (Brophy, 2002(Brophy, , 2005Guilbault, 2004Guilbault, , 2009Kratus, 1989;Paananen, 2006Paananen, , 2007Tafuri, Baldi, & Caterina, 2003). Melodic, rhythmic, and structural content were all variables of interest along with tonality, accompaniment type, and motivic repetition.…”
Section: Development Of Improvisation Skills With Agementioning
confidence: 99%
“…Children can learn musical conventions and structures through environmental exposure to music (Tafuri et al, 2003). Children spontaneously differentiate sound qualities during free imaginative play, where there are no strict rules and they are not foreseeing what they still 'do not know'.…”
Section: Musical Vibrational Instruments and Early Educationmentioning
confidence: 99%
“…Children can learn musical conventions and structures through environmental exposure to music (Tafuri et al, 2003). Children spontaneously differentiate sound qualities during free imaginative play, where there are no strict rules and they are not foreseeing what they still 'do not know'.…”
Section: Musical Vibrational Instruments and Early Educationmentioning
confidence: 99%